Determining the best immunization strategy for protecting African children against invasive Salmonella disease - Jeon, HJ; Pak, GD; Im, J; Owusu-Dabo, E; Adu-Sarkodie, Y; Sow, A; Bassiahi, AS; Gasmelseed, N; Keddy, KH; Bjerregaard-Andersen, M; Konings, F; Aseffa, A; et al. (Oxford University Press, 2018)
Background The World Health Organization recently prequalified a typhoid conjugate vaccine (TCV), recommending its use in persons ≥6 months to 45 years residing in typhoid fever (TF)–endemic areas. We now need to consider how TCVs can have the greatest impact in the most vulnerable populations. Methods The Typhoid Fever Surveillance in Africa Program (TSAP) was a blood culture-based surveillance of febrile patients from defined populations presenting at healthcare facilities in 10 African countries. TF and invasive non-typhoidal Salmonella (iNTS) disease incidences were estimated for 0–10 year-olds in one-year age increments. Results Salmonella Typhi and iNTS were the most frequently isolated pathogens; 135 and 94 cases were identified, respectively. Analysis from three countries was excluded (incomplete person-years of observation (PYO) data). Thirty-seven of 123 TF cases (30.1%) and 71/90 iNTS disease cases (78.9%) occurred in children aged <5 years. No TF and 8/90 iNTS infections (8.9%) were observed in infants aged <9 months. The TF incidences (/100 000 PYO) for children aged <1 year and 1 to <2 years were 5 and 39, respectively; the highest incidence was 304 per 100 000 PYO in 4 to <5 year-olds. The iNTS disease incidence in the defined age groups ranged between 81 and 233 per 100 000 PYO, highest in 1 to <2 year-olds. TF and iNTS disease incidences were higher in West Africa. Conclusions High burden of TF detected in young children strengthens the need for TCV introduction. Given the concurrent iNTS disease burden, development of a trivalent vaccine against S. Typhi, S. Typhimurium, and S. Enteritidis may be timely in this region.